Measurement of Natural and Artificial Radioactive Elements in Soil at the Southern Al-Dora Region, Baghdad Governorate, Iraq - Rejah, Basim Khalaf; Oraibi, Afrah Hassoon; Al-Salihi, Abdalrahman (Journal of natural sciences, life and applied sciences, 2020)
The specific activity of natural and artificial radioactive elements in nine soil samples at different locations of southern Al-Dora region, Baghdad governorate, Iraq were measured and analysed by using a gamma ray detector NaI (Tl). The average activity concentrations of 238U, 232Th, 40K and 137Cs are found to be 38.22 Bq/Kg, 42.99 Bq/Kg, 16.64 Bq/Kg and 2.92 Bq/Kg, respectively. Several radiological hazard indices including radium equivalent activity (Raeq), absorbed dose rate (D), internal (Hin) and external (Hex) hazard indices, internal (AEDEin) and external (AEDEex) annual effective dose equivalent and gamma ray index (Iγr) are calculated. The findings of all radiological hazard indices are lower than their international values. This study discloses that most locations in study area are safe from any radiological risks.